Incidence of Cardiac Arrhythmia in Chronic Cor Pulmonale with Special Reference to its Etiology - Nayak, Jadumani; Naik, Manoranjan; Panda, Smaraka R; Behera, Sudeshna (Asian Journal of Medical Sciences, 2013)
Objective: to evaluate the incidence of cardiac arrhythmia in chronic cor pulmonale and to focus on the contributing etiological factors. Material & Methods: 35 cases of chronic cor pulmonale were thoroughly examined for the presence of arrhythmia. After recording history & physical examination blood was collected for various investigations like serum potassium, blood urea, blood volume and ABG study before and after the development of arrhythmia. Along with this X-ray & ECG were done in every case. Results: incidence of cardiac arrhythmia among all cor pulmonale patients was found to be 20% of which supraventricular ectopic beats was the most common. Respiratory infection may be thought to be the major factor in the development of congestive heart failure & different cardiac dysarrhythmia. Besides this, not a single possible factor has been found to be associated with cardiac arrhythmia. Conclusion: cor pulmonale has a low incidence in this part of country. Not a single factor associated with cardiac arrhythmia could be found out except pulmonary infection. Further studies are required in this field on a larger number of patients. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8393 Asian Journal of Medical Science Vol.5(1) 2014 pp.15-19